Spectrophotometric comparison of two porcelain systems, VMK master and VM13 with the VITA 3D-master shade guide (An in vitro study) - Assadollah Ahmadzadeh; Sara Mansourinejad; Sanaz Mansourinejad; Ali Rohani (Wolters Kluwer Medknow Publications, 2022)
Background: Accurate shade matching of metal-ceramic restorations with natural teeth is one of the most challenging aspects of dental restorations and esthetic dentistry. The aim of this study was to evaluate of the color parameters of two types of porcelain systems VMK Master and VM13 porcelain with VITA 3D-master shade guide. Materials and Methods: In this in vitro study a total of 56 metal discs (10 mm diameter and 2 mm thickness) were fabricated. Each of the disks was veneered with porcelain (Vita Zahnfabrik, Bad Sackingen, Germany) of the VITA shade. The discs were randomly divided into four groups (2M2 and 3M2 from VM13, 2M2 and 3M2 from VMK master) of 14 (n = 14). The spectrophotometer was used for taking color measurements based on the numerical color data of the CIELAB color system. Data analysis was performed by t-test (P < 0.05). Results: Comparison of color parameters in different porcelain showed that the type of porcelain caused a significant difference in color parameters (L, a, and b) (P < 0.05). The degree of translucency (L*) or glaze of VMK porcelains was higher than VM13, but the parameters a* and b* were higher in VM13 porcelains than VMK (P < 0.05). Furthermore, the color difference of two porcelain in 2M2 (1.63 ± 0.84) and 3M2 (1.71 ± 0.96) shades was within the acceptable clinical limit. Considering the total color difference (ΔE), there were no significant differences between the ΔE values produced by any of shades (P > 0.05). Conclusion: In the present study, the spectrophotometric analysis revealed that the porcelain shade type causes a change in the color parameters, but the color difference between two porcelains VMK and VM13 is within the acceptable range of clinical color. Therefore, both porcelain systems with 2M2 and 3M2 shades are suitable for enhancing the results of restorative dentistry.